2011
DOI: 10.1149/1.3602192
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Crystallization Velocity in Explosive Crystallization of Amorphous Silicon Films Induced by Flash Lamp Annealing

Abstract: We propose a new method to estimate the explosive crystallization (EC) velocity (v EC ) of amorphous silicon (a-Si) films using multi-pulse flash lamp annealing (FLA). This system produces discrete pulses at frequencies of 1-10 kHz to form a quasi-millisecond pulse. The multi-pulses leave behind macroscopic stripe patterns on the surfaces of polycrystalline Si (poly-Si) films, the widths of which are indications of v EC . We find that catalytic chemical-vapor-deposited (Cat-CVD) and sputtered a-Si films show v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 22 publications
4
42
0
Order By: Relevance
“…We have confirmed that the quasi-millisecond pulse can induce the crystallization of a-Si films equivalent to conventional single-pulse FLA [15]. Furthermore, the cyclic temperature modulation of Si films induced by discrete pulses during quasi-millisecond pulse emission results in the formation of macroscopic stripe patterns on FLC poly-Si films, the interval of which yields the velocity of EC (v EC ) [15]. The crystallization of a-Si films was evaluated by Raman spectroscopy and X-ray diffraction (XRD).…”
Section: Methodssupporting
confidence: 59%
See 2 more Smart Citations
“…We have confirmed that the quasi-millisecond pulse can induce the crystallization of a-Si films equivalent to conventional single-pulse FLA [15]. Furthermore, the cyclic temperature modulation of Si films induced by discrete pulses during quasi-millisecond pulse emission results in the formation of macroscopic stripe patterns on FLC poly-Si films, the interval of which yields the velocity of EC (v EC ) [15]. The crystallization of a-Si films was evaluated by Raman spectroscopy and X-ray diffraction (XRD).…”
Section: Methodssupporting
confidence: 59%
“…We then performed FLA onto each a-Si film under stage pre-heating by a halogen lamp at 500 1C. The FLA system supplies a quasi-millisecond pulse consisting of discrete sub-pulses at emitted tunable frequencies of 1-10 kHz [15]. We have confirmed that the quasi-millisecond pulse can induce the crystallization of a-Si films equivalent to conventional single-pulse FLA [15].…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…We have confirmed the crystallization of Si films by Raman spectroscopy. The typical Raman spectrum of a flash-lamp-crystallized (FLC) poly-Si film is seen in a previous paper [25]. We observed no significant differences in Raman peak width, peak position (~520.5 cm − 1 ), and crystalline fraction for FLC poly-Si films formed on various glass substrates, meaning that the FLC poly-Si films have similar microstructures and stresses.…”
Section: Methodssupporting
confidence: 72%
“…1. The details of the FLA system have been summarized elsewhere [25]. We have confirmed the crystallization of Si films by Raman spectroscopy.…”
Section: Methodsmentioning
confidence: 54%